قياس مدركات العاملين في مشفى الشهيد محمد وسيم معاذ لواقع ممارسات الإدارة بالتجوال: دراسة ميدانية - حمادة، عبدالله; عريض، محمود علي; حايك، عبدالحليم عبدالغني (مركز البحث وتطوير الموارد البشرية - رماح, 2020)
هدفت الدراسة إلى قياس مدركات العاملين في مشفي الشهيد محمد وسيم معاذ لواقع ممارسات الإدارة بالتجوال بأبعادها المختلفة (اكتشاف الحقائق، تحسين الاتصال التحفيز، التطوير والإبداع، التغذية العكسية)، وكذلك التعرف على الفروق الموجودة بين العاملين في إدراكاتهم لممارسات الإدارة بالتجوال تبعا لاختلاف بعض المتغيرات الديمغرافية والوصفية، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي التحليلي، حيث طبقت الدراسة على عينة قوامها (250) مفردة تم اختيارهم بطريقة عشوائية، تم استرداد (190) استبانة، وبهذا بلغت نسبة الإستراد (76%)، وقام الباحثون باستبعاد (3) استبانات لعدم كفاية البيانات فيها، وتم اعتماد (187) استبانة من أجل التحليل الإحصائي. وقد أظهرت النتائج أن تطبيق ممارسات الإدارة بالتجوال في مشفي الشهيد محمد وسيم معاذ كانت مرتفعة، كما أظهرت النتائج وجود فروق ذات دلالة إحصائية في ممارسات الإدارة بالتجوال تعود لسنوات الخبرة، في حين لم تظهر الدراسة أي فروق ذات دلالة إحصائية في ممارسات الإدارة بالتجوال تعود لمتغيرات (النوع، طبيعة العمل). The study aimed to measure the perceptions of workers in the hospital of the martyr Muhammad Waseem Moaz for the reality of Practices of Management by Walking Around (discovering facts, improving communication, motivation, development and creativity, feedback), as well as identifying the differences between workers in their perceptions of Practices of Management by Walking Around according to the difference in some demographic variables Descriptive(gender-field work-experience), and to achieve the objectives of the study, the descriptive analytical approach was used, as the study was applied to a sample of (250) individuals who were randomly selected, (190) questionnaires were returned, and thus the percentage of redemption reached (76%), and the researchers excluded (3) questionnaires. Because of insufficient data, (187) questionnaires were approved for statistical analysis. The results showed that the application of Practices of Management by Walking Around in the hospital of the martyr Muhammad Waseem Moaz was high, as the results showed that there were statistically significant differences in Practices of Management by Walking Around back to years of experience, while the study did not show any statistically significant differences in Practices of Management by Walking Around due to variables (gender, field of work).
Keywords: الإدارة بالتجوال -- القيادة الإدارية -- الرضا الوظيفي -- التغذية الراجعة -- المؤسسات الصحية